Rancang Bangun Aplikasi Sistem Informasi Peserta Didik Baru menggunakan PHP dan Mysql â€œSman 3 Selongâ€ - Saiful, Muhammad; Amalia, Nurfitri (Fakultas Teknik Universitas Hamzanwadi, 2018)
The existence and role of information technology without us realizing it has entered a new era. One of the needs of educational institutions and government in the provision of information facilities is computerized technology-based information, where systems that have used computerization have a much faster level of reliability and more efficient data processing compared to manual systems. SMAN 3 Selong is a public high school which in the processing of new student admission data still does not use a specific application, so that the results of work achieved are not maximal and take a long time. Therefore, an information system for the recruitment of prospective students is made so that it is easier to filter and receive new students. The method used in this study is to conduct literature studies and conduct system tests. The programming language used in making this information system is PHP-MySQL. The results achieved in this study are the formation or creation of a web-based information system that is used to recruit new students. With this information system, it is expected that the work system can be more assisted and the application of development and utilization of technology is maximized.DOI : 10.29408/jit.v1i1.891